Impacts of family care for children and the elderly on women’s employment: evidence from rural China - Miao, Xinru; Han, Jiqin; Wang, Shaopeng; Han, Bing (Frontiers in Psychology, 2023)
China's traditional culture makes rural women and men take on different family responsibilities. Use "China Family Panel Studies" (CFPS) data and build Logit and propensity score matching models to empirically study the impact of children care and elderly care on rural married women going out to work. And explore the welfare effects of basic education public services in helping rural women take care of their families. The results show that caring for children has a significant hindering effect on rural married women's job hunting. Especially for those in low-income families, the employment inhibition is most significant among women aged 20-30 with multiple children. Contrary to previous cognition, supporting the elderly has a certain weak stimulating effect. The kindergarten public services in rural areas can help women take care of their children and relieve their work pressure. The primary school public services have not played a role in alleviating them. This shows that there are still a large number of female laborers in rural China who are unable to go out to work due to family care. The improvement of rural basic education public services can promote more rural women going out to work. This finding will provide a policy reference for the introduction of a formal care system and the establishment of basic education public services in China.